Impact of COVID-19 lockdowns on STEMI percutaneous interventions. (14th October 2021) - Zlochiver, V; Perez Moreno, A C; Hall, J; Hommeida, M; Allaqaband, S Q; Bajwa, T; Jan, M F
Abstract: Background: Measures taken to mitigate the spread of coronavirus disease 2019 (COVID-19) have been correlated to a decline in the number of patients seeking medical care for emergency cardiovascular illness. Here we evaluate the impact of a state-wide lockdown on ST-elevation myocardial infarction (STEMI) care. Purpose: The purpose of this study is to help understand the impact of COVID-related lockdowns on STEMI interventions. Methods: All consecutive adult patients admitted with an acute STEMI diagnosis and percutaneous intervention (PCI) performed between January 17, 2020, and July 14, 2020, at five sites across our health care network, were included in this study. Patient demographics, medical history and procedure details were collected retrospectively from electronic medical records. Data were segregated according to date into pre-lockdown, lockdown (March 17 to May 13, 2020) and post-lockdown groups. Results: A total of 225 patients formed the study cohort. Median age was 62 (IQR: 53–71) years. Patients were predominantly male (n=154, 68%), white (n=208, 92%), hypertensive (n=139, 61%) and dyslipidemic (n=135, 60%). The average weekly rate of STEMI PCIs performed pre-lockdown decreased by 40% during the lockdown from 10.9 to 6.5 PCIs per week (p<0.05). Door-to-balloon (D2B) times increased from 42 (IQR: 28–68) min pre-lockdown to 53 (IQR: 40–72) min during the lockdown (p=0.01). No significant differences were observed in in-hospital mortality or cardiac troponin measurements within 24 h of procedure between the three groups. Conclusion: Adverse effects of COVID-19-related lockdowns on acute STEMI care include a decrease in PCI volumes and prolonged D2B times. Our results provide valuable data-driven criteria to help inform patient decisions to seek care and to find ways to protect healthcare workers without compromising timely critical intervention. FUNDunding Acknowledgement: Type of funding sources: None.